2006
DOI: 10.1111/j.1365-2141.2006.06417.x
|View full text |Cite
|
Sign up to set email alerts
|

Severity of pulmonary hypertension during vaso‐occlusive pain crisis and exercise in patients with sickle cell disease

Abstract: Summary Pulmonary hypertension is associated with sudden death and is a risk factor for mortality in adult patients with sickle cell disease. The high mortality despite only mild‐to‐moderate increases in pulmonary vascular resistance remains an unresolved paradox. Accordingly, little is known about the cardiovascular effects of stressors, such as vaso‐occlusive pain crisis (VOC) and exercise, which may acutely increase pulmonary pressures and impair right heart function. We therefore evaluated pulmonary artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 44 publications
(46 reference statements)
4
87
0
2
Order By: Relevance
“…6,11 The present study was prospective, included children as young as 3 years of age with mild to severe sickle phenotypes, and avoided effects of exercise or acute vaso-occlusive crisis, known to be confounding factors for the determination of steady state jet velocity in patients. 27 In particular, patients who were hospitalized in the preceding 3 weeks could not be enrolled and this …”
Section: Discussionmentioning
confidence: 99%
“…6,11 The present study was prospective, included children as young as 3 years of age with mild to severe sickle phenotypes, and avoided effects of exercise or acute vaso-occlusive crisis, known to be confounding factors for the determination of steady state jet velocity in patients. 27 In particular, patients who were hospitalized in the preceding 3 weeks could not be enrolled and this …”
Section: Discussionmentioning
confidence: 99%
“…Various markers of hemolysis, such as plasma LDH concentration, reticulocyte count, plasma arginase activity and hemoglobin, have been correlated with pulmonary hypertension in those patients [40]. A recent study in SCD patients showed that pulmonary artery pressure and pulmonary vascular resistance were increased during vaso-occlusive crises in parallel to hemolysis and hemoglobin level drop [41]. This correlation may represent the functional component of a strong hemolytic effect on the top of chronic lung vascular injury, an injury that may vary according to patients' age.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that in our SCA mice, LAE is a downstream consequence of microscopic myocardial fibrosis, leading to ventricular diastolic dysfunction and in turn, impaired LA emptying and LA hypertension. Restrictive LV filling and LA hypertension may lead to elevated pulmonary venous pressure, a feature associated with increased TRV in patients with SCA (18,65,66).…”
Section: Berk-ss Mice Develop Corrected Qt Prolongation and Widening mentioning
confidence: 99%